Post-Post-Kemalizm: Türkiye Çalışmalarında Yeni Arayışlar - Haksever, Oğuz Ufuk (My University, 2024)
Post-Post-Kemalizm: Türkiye Çalışmalarında Yeni Arayışlar (Post-Post-Kemalism: Search for Alternatives in Turkish Studies), edited by İlker Aytürk and Berk Esen, aims to present a multidimensional approach to a long-standing intellectual debate in the field of Turkish studies. As laid out by the editors in the preface, the book is based on the argument that the post-Kemalist paradigm is insufficient for making sense of Türkiye today, which prompts the search for an alternative paradigm (p. 14). The book, which consists of two sections, first details the failure of the post-Kemalist paradigm as seen through different disciplines, including political science, women’s studies, and foreign policy. The second part then provides a rethinking of the paradigm by presenting a critique of post-Kemalism from different thematic perspectives, including liberalism, culturalism, secularism, tutelage,1 Islamic studies, and political parties. The work aims to create an alternative perspective to contemporary Turkish studies and provides benefit to researchers who are interested in and are carrying out studies in this field.
Keywords: Turkey; Kemalism; Turkish politics